383Pneumococcal conjugate vaccine is effective against hypoxic pneumonia in Laos, Mongolia and Papua New Guinea. (2nd September 2021) - Nguyen, Cattram; Weaver, Rupert; Blyth, Christopher; Mollendorf, Claire von; Britton, Kate; Chan, Jocelyn; Dance, David A B; Ford, Rebecca; Lai, Jana Y R; Mungun, Tuya; Newton, Paul; Mulholland, Edward Kim; et al.
Abstract: Background: We describe a novel approach to determine PCV13 effectiveness (VE) against hypoxic pneumonia in children admitted with pneumonia in Lao People's Democratic Republic (Laos), Mongolia and Papua New Guinea (PNG). Methods: A 3-5 year prospective hospital-based observational study of children < =59 months admitted with pneumonia was undertaken. Pneumonia was defined using the 2013 WHO definition. Hypoxia was defined as an oxygen saturation <90% in room air or requiring oxygen supplementation during hospitalisation. PCV13 status was determined by written record. VE was calculated using logistic regression comparing the odds of hypoxia between vaccinated and under-vaccinated pneumonia cases. To handle potential confounding, a propensity score (PS) analysis using inverse probability of treatment weighting (IPW) was used. In Laos, multiple imputation (MI) analysis was undertaken for missing data. Results: The VE against hypoxic pneumonia were: in Laos, unadjusted 23% (95% CI: -9, 46%; p = 0·14), IPW adjusted 37% (6, 57%; p = 0.02), MI and IPW adjusted 35% (7, 55%; p = 0.02); in Mongolia, unadjusted 33% (26, 40%; p < 0.001), IPW adjusted 33% (16, 47%; p < 0.001); and in PNG, unadjusted 6% (-15, 24%; p = 0.53), IPW adjusted 36% (17, 51%; p = 0.001). Conclusions: Our novel approach shows that PCV13 is effective against hypoxic pneumonia. PCV13 will contribute to reducing child mortality. Key messages: We describe a novel, single hospital-based approach for determining VE that can be applied to other similar settings. This is one of the first studies showing PCV13 to be effective against hypoxic pneumonia in children in Asia.